OWE-24 CT colonography in national bowel screening program, is it reducing the burden?. (June 2019) - Elkady, Soad; Muller, Andrew
Abstract : Introduction: CT Colonography (CTC) or virtual colonoscopy offers an effective non-invasive technique to assess the bowel if conventional colonoscopy fails or is not done due to patients' factors. Aim of the work: To identify if CTC can actually help decrease the burden by decreasing the number and type of endoscopy required especially in patients with multiple comorbidity. Methods: We reviewed CTC requested for patients in the National bowel screening program over a period of 9 years from end of 2009 till beginning of 2018. Post CTC colonoscopy was reviewed and results assessed. Results: 220 CTC procedures were requested over the study period for 206 patients. Most patients (194) required one CTC, ten patients had it twice and two patients had it three times. Age of the patients at the time of the procedure ranged between 60 years to 81 years old. 60% were female versus 40% male. Most common indications for the CTC were failed endoscopy in 56%, patients with multiple comorbidities 15% and patient preference in 7% of cases. Colonic pathology was reported in 68% (149) of the cases, extra-colonic in 21% (47) and no pathology identified in 10% (21) of the cases. Colonic pathology included colonic masses, polyps, stricture and diverticular disease. Important extra-colonic findings reported included metastatic disease, abdominal aortic aneurysm, fatty liver, renal and liver cysts. Only 61(28%) cases had a post CTC endoscopy within maximally 1 year interval. Most were sigmoidoscopy 41(67%), followed by colonoscopy 14 (23%). Deep sedation was required for 5 cases (8%); 3 were colonoscopy and 2 were sigmoidoscopy. 15 (7%) cases were reported by CTC as suggestive of colonic mass. Only 9 had a post CTC endoscopy; of which only 2 were found to have colonic mass. Colonic polyps and diverticular disease was found in 3 cases and no pathology identified in the remaining 3. 51 (23%) cases were reported by CTC to have colonic polyps 41 had post CTC endoscopy of which 31 (76%) were found to have polyps and polypectomy performed. One case (2%) was found to have colonic mass. 5 (12%) had only diverticular disease and one with telangiectasia and in 3 (7%) cases no pathology was identified. Conclusions: CTC was useful guide to direct further management of the patients as regards any endoscopy being requested at all and type being mainly simple sigmoidoscopy in most of the cases. Combination of CTC with faecal occult blood in BSP could be a reasonable alternative for patient's assessment especially those elderly group with multiple comorbidities and challenging endoscopy.